Upper extremity deep venous thrombosis and stenosis after implantation of pacemakers and defibrillators; A prospective study - Safi Morteza; Akbarzadeh Mohammad Ali; Azinfar Azadeh; Namazi Mohammad Hasan; Khaheshi Isa (Sciendo, 2017)
Background. Obstruction of the access vein following cardiac pacemaker and defibrillator implantation is a common complication. However, the exact incidence and contributing risk factors are unknown. The aim of this study is to determine the incidence and analyze the contribution of each risk factor. Methods. 57 consecutive patients candidate for their first transvenous pacemaker, implantable cardioverter-defibrillator (ICD), or cardiac resynchronization therapy device implantation were enrolled. After implantation, venography of the ipsilateral peripheral arm was performed. Patients underwent their second venography after the follow-up period of 3 to 6 months. Results. 42 patients (13 females, mean age 59.71 ± 12.33) completed the study. The followup venography showed significant venous obstruction (more than 50%) in 9 (21%) patients, but in none of the individuals, venography revealed total occlusion of the veins. Patients with obstruction had more leads in their veins (2.56 ± 0.53 vs 1.58 ± 0.71, P = 0.001). Venous obstruction was significantly more prevalent in patients with implanted cardiac resynchronization therapy device compared with an ICD or pacemaker (p = 0. 01). Age, gender, diabetes mellitus, hypertension, ischemic heart disease and antiplatelet consumption did not reveal any other contribution to the risk of thrombosis. In multivariate analysis, total lead number was a positive predictor for venous occlusion (P = 0.015, OR:19.2, and CI: 1.7-207.1). Conclusion. Venous obstruction is relatively frequent after pacemaker or ICD implantation. This study also shows that pacemaker and ICD leads have a similar risk for lead-related venous obstruction. However, patients with multiple leads are associated with an increased risk.